Efficient regeneration and transformation of plantain cv. Gonja manjaya" (Musa spp. AAB) using embryogenic cell suspensions" - Tripathi, J.N.; Muwonge, A.; Tripathi, L. (Springer, 2012)
In banana and plantain research, it is essential to establish embryogenic cell suspensions together with a highly efficient regeneration and transformation system. This article describes the development of an embryogenic cell suspension (ECS), regeneration, and transformation for plantain cv. “Gonja manjaya”. ECS was established using highly proliferative multiple buds. The frequency of embryogenic friable callus formation was 56.8% of the cultured explants. Friable embryogenic calli with many translucent proembryos were transferred to liquid medium and homogenous cell suspensions were established within 3–4 mo. Approximately 25,000 to 30,000 plants per 1.0 ml of settled cell volume were regenerated in approximately 13–14 mo. ECSs were transformed using Agrobacterium strain EHA 105 harboring the binary vector pBI121. About 50–60 transgenic plants per 0.5 ml settled cell volume were regenerated on selective medium containing 100 mg l−1 kanamycin. Histochemical GUS assays using different tissues of putatively transformed plants demonstrated stable expression of uidA gene. The presence and integration of the uidA gene were confirmed by PCR and Southern blot analysis, respectively. This is the first report showing establishment of embryogenic cell suspension cultures and Agrobacterium-mediated transformation of an important plantain cultivar, “Gonja manjaya”. This study shows the huge potential for genetic transformation of plantains for disease or pest resistance, as well as tolerance to abiotic factors such as drought stress using this robust regeneration and transformation protocol.